Spatial Analysis of Rice Field Development in Supporting Sustainable Food Security in West Muna Regency - Taridala, Sabrillah; Fadli Ode, Muhamad; Hiromi, Rahma; Amin, Haidir; Mukaddas, Jamal; Harudin, La; Tao, Haerudin; Sawaludin, Sawaludin; Oge, La; Inal, Inal; Alim Padar, Sekar; Alwan, Alwan; et al. (International Journal of Management and Education in Human Development, 2024)
This research aims to spatially analyze the development of rice fields to support sustainable food security in West Muna Regency. With a qualitative and quantitative analysis approach, this research identifies local potential as well as the obstacles faced by the agricultural sector. This research also examines agricultural area development strategies to support food security in West Muna Regency, Southeast Sulawesi, using both qualitative and quantitative approaches to obtain a comprehensive picture. The data used consists of primary data obtained from field surveys and observations, while secondary data is obtained from documentation studies in the form of literature related to the focus of the study. The data analysis techniques used are: (1) descriptive analysis; (2) Location Quotient (LQ) analysis; (3) spatial analysis using the ArcGIS application. The determination of zoning for rice productivity improvement consists of: (1) Intensive production zones for productivity enhancement, namely Sawerigadi (590 ha), South Tiworo (822 ha), Central Tiworo (169 ha), Maginti (150 ha), Tiworo Islands (258 ha); (2) Extensive development zones, namely Kusambi (10,263 ha), Wadaga (12,605 ha), and Lawa (8,492 ha); (3) Agribusiness infrastructure support zones, namely Sawerigadi (590 ha) as the agribusiness center, Barangka (3,132 ha), Lawa (8,492 ha), and Wadaga (12,605 ha) as centers for agricultural product distribution. The construction of new irrigation systems in districts such as Wadaga and Kusambi is very important for increasing productivity. Improvement of connecting roads between the districts of Barangka, Lawa, Wadaga, and Sawerigadi to facilitate the distribution of harvests. The strategy for rice field development includes; (1) Strengthening intensive production zones; (2) Extensification of new land; (3) Development of agribusiness infrastructure; (4) Empowerment of farmers and market access; (5) Climate change adaptation; and (6) Integration of agro-tourism based on rice cultivation. With these strategic steps, the agricultural sector of West Muna Regency is expected to support food security and community welfare sustainably and reduce dependence on food supply from outside the region.